Aberrant T Helper 17 Cells and Related Cytokines in Bone Marrow Microenvironment of Patients with Acute Myeloid Leukemia. (18th August 2013) - Tian, Tian; Yu, Shuang; Wang, Min; Yuan, Cunzhong; Zhang, Hua; Ji, Chunyan; Ma, Daoxin
Abstract : In this study, we mainly investigate the role of Th17 cells, Th1 cells, and their related cytokines in the pathophysiology of AML. BM and PB were extracted from ND, CR, and relapsed-refractory AML patients and controls. Th subsets frequencies were examined by flow cytometry. BM plasma Th-associated cytokines levels were determined by ELISA. The frequencies of Th17 and Th1, and IFN- γ or TGF- β concentrations were significantly decreased in ND compared with CR patients or controls. Th17 percentage was significantly lower in BM than in PB for ND patients but was higher in BM for CR patients. However, in CR or relapsed-refractory patients, Th1 percentage in BM was higher than that in PB. Moreover, BM IL-17A level showed a decreased trend in ND patients. A significant elevation of plasma IL-6 level was found in ND compared with CR patients or controls. IL-17A showed the positive correlation with IL-6 concentration. And Th17 cells frequencies and TGF- β 1 concentration were increased in BM from AML patients achieving CR after chemotherapy. Moreover, a significant decrease of BM plasma TGF- β 1 level was found in M3 patients compared with the other subtypes. Our findings suggest that Th17 and related cytokines may be implicated in AML pathogenesis.